Effectiveness of Interventional Package on Pulmonary Functional Parameters Among Patients with Chronic Obstructive Pulmonary Disease Admitted in Selected Medical College and Hospital - Malathi, G.; Sarathi, Sathiyalatha; Hemavathy, V. (European Journal of Applied Sciences, 2024)
Chronic Obstructive Pulmonary Disease is very common in general population. It is a slowly progressing disease involving the airways or pulmonary parenchyma resulting in airflow obstruction. The most common factor leading to COPD is cigarette smoking, exposure to occupational dust and chemicals. The symptom of COPD ranges from dyspnoea, chronic cough with or without sputum production. Interventional package containing education and deep breathing exercises improved the health status and increased the exercise tolerance of patients with COPD. The main objective of the study was to determine the effectiveness of interventional package on pulmonary functional parameters among patients with chronic obstructive pulmonary disease in experimental group. The research design adopted was quasi experimental with two group pre test post test design. Purposive sampling technique was followed to obtain a sample of 400 COPD patients (200 COPD patients in experimental groups and 200 COPD patients in control groups) Pre test and post test assessment was done by using pulmonary functional parameters.Interventional package containing educational phase was provided for 15-20 minutes daily and deep breathing exercises were administered 2 cycles per day for 7 days to the experimental group whereas control group was not given any intervention. Post test was conducted after intervention both experimental and control group on day 7. The study reveals that they improves the pulmonary functional parameters after intervention, than in the control group. The t value of difference of comparison mean of pulmonary function tabulated was found to be t=28.45, df = 59 P<0.05. The study also shows that there is an association between age, history of smoking, family history, the conclusion of the study shows that interventional package is found to be an effective non pharamacological therapy to improve lung function.